Isolation, identification, and serotyping of Avibacterium paragallinarum from quails in Indonesia with typical infectious coryza disease symptoms - Agnesia Endang Tri Hastuti Wahyuni; Charles Rangga Tabbu; Sidna Artanto; Dwi Cahyo Budi Setiawan; Sadung Itha Rajaguguk (Veterinary World, 2018)
Background and Aim: Infectious coryza (IC) or snot is an infectious upper respiratory disease affecting chickens and birds, including quails, and it is caused by Avibacterium paragallinarum. The symptoms of IC are facial swelling, malodorous nasal discharge, and lacrimation. This study aimed to isolate, identify, and serotype the A. paragallinarum of snot in quails and to determine the sensitivity and resistance to several antibiotics.